Evaluasi Ketersediaan Pelayanan Informasi Obat Resep Glibenklamid sebagai Anti Diabetes Oral di Apotek-Apotek Wilayah Kabupaten Sleman DIY - Djunarko, Ipang; Butar-Butar, Iryana (Jurnal Sains dan Teknologi Farmasi, 2012)
This study aimed at describing glibenclamide prescription service profile which includes the availability of glibenclamide prescription information services provided by pharmacist at the pharmacy as well as the availability and completeness of the prescription copies and the drug label. This study was non-experimental study or observational descriptive study design through Participatory observation Partial. The data obtained included type of drug information provided, copy of prescription, drug label, and the status of prescribing provider,which were analyzed by descriptive statistics. From 124 sample of pharmacies, 3 (2,43%) pharmacies refused to serve prescription. Profil of prescription service given : 30 (24,19%) pharmacies returned the prescription, 4 (3,23%) refused making copy of prescription, 1 (0,81%) pharmacy didnât provide medicine appropriately with prescription, 21 (16,94%) didnât attach drug label, 8 (6,45%) didnât provide drug information service, and 53 (42,74%) pharmacies didnât conduct the prescription service by competent pharmacist. From the amount of 113 which provide drug information service, there was no pharmacy give drug information service completely based on Kepmenkes RI No. 1027 tahun 2004.